Pengaruh Senam Asma Terhadap Kualitas Hidup Dan Kepatuhan Minum Obat Pada Penderita Asma - Andre Utama Aaputra; Yulinda Ariyani; Ranida Arsi; Yeni Elviani (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Asthma is a chronic inflammatory disease of the respiratory tract and is a world health problem not only in developed countries but also in developing countries.This type of research is a quasi-experimental with a quasi-experimental design with a pretest-posttest design with a control group design. The population in this study were asthma patients at the Pematang Panggang IV Health Center Mesuji Raya OKI based on medical record data for 2022 new patients so that a total sample of 100 patients, with a sampling technique using purposive sampling and calculations using the Slovin formula to obtain 50 respondents with each both the intervention and control groups, namely as many as 25 people. The results showed that there was an increase in the average value (mean) both in quality of life and adherence to taking medication in asthma patients between before and after being given asthma exercise in the intervention group respondents. Based on the results of the independent sample t-test, it shows that there is an effect of asthma exercise on the quality of life of asthma patients in the working area of ​​the Pematang Panggang IV Health Center as evidenced by a significance value of 0.018 (sig <0.05). Likewise, there is an effect of asthma exercise on medication adherence of asthma patients in the working area of ​​Pematang Panggang IV Health Center as evidenced by a significance value of 0.027 (sig <0.05)